Development, current state and future trends of sludge management in China: Based on exploratory data and CO2-equivaient emissions analysis. (November 2020) - Wei, Liangliang; Zhu, Fengyi; Li, Qiaoyang; Xue, Chonghua; Xia, Xinhui; Yu, Hang; Zhao, Qingliang; Jiang, Junqiu; Bai, Shunwen
Graphical abstract: Highlights: Sludge production in China in 2019 was 39.0 million tons, average 28.1 kg/y per capita. Higher reginal urbanization rate and GDP led to a higher per capita sludge production. Spatial/temporal trends of sludge treatment/disposal techniques were investigated. Incineration in East China accounted 31.3% of GHG emission of sludge disposal in 2019. Discrepancy, challenges and future perspectives of sludge disposal in China was analyzed. Abstract: This study statistically reported the current state of sludge treatment/disposal in China from the aspects of sources, technical routes, geographical distribution, and development by using observational data after 1978. By the end of 2019, 5476 municipal wastewater treatment plants were operating in China, leading to an annual sludge productivity of 39.04 million tons (80% water content). Overall, 29.3% of the sludge in China was disposed via land application, followed by incineration (26.7%) and sanitary landfills (20.1%). Incineration, compost, thermal hydrolysis and anerobic digestion were the mainstream technologies for sludge treatment in China, with capacities of 27, 122, 11, 250, 8342 and 6944 t/d in 2019, respectively. Incineration and drying were preferentially constructed in East China. In contrast, sludge compost was most frequently used in Northeast China (46.5%), East China (22.4%) and Central China (12.8%), while anaerobic digestion in East China, North China and Central China. The capacities of sludge facilities exhibited a sharp increase in 2009–2019, with an overall greenhouse gas emissions in China in 2019 reached 108.18 × 10 8 kg CO2 -equivaient emissions, and the four main technical routes contributed as: incineration (45.11%) > sanitary landfills (23.04%) > land utilization (17.64%) > building materials (14.21%). Challenges and existing problems of sludge disposal in China, including high CO2 emissions, unbalanced regional development, low stabilization and land utilization levels, were discussed. Finally, suggestions regarding potential technical and administrative measures in China, and sustainable sludge management for developing countries, were also given.